Linking late Paleoindian stone tool technologies and populations in North, Central and South America. - Keith M Prufer; Asia V Alsgaard; Mark Robinson; Clayton R Meredith; Brendan J Culleton; Timothy Dennehy; Shelby Magee; Bruce B Huckell; W James Stemp; Jaime J Awe; Jose M Capriles; Douglas J Kennett (PLoS ONE, 2019)
From the perspective of Central and South America, the peopling of the New World was a complex process lasting thousands of years and involving multiple waves of Pleistocene and early Holocene period immigrants entering into the neotropics. These Paleoindian colonists initially brought with them technologies developed for adaptation to environments and resources found in North America. As the ice age ended across the New World people adapted more generalized stone tools to exploit changing environments and resources. In the neotropics these changes would have been pronounced as patchy forests and grasslands gave way to broadleaf tropical forests. We document a late Pleistocene/early Holocene stone tool tradition from Belize, located in southern Mesoamerica. This represents the first endogenous Paleoindian stone tool technocomplex recovered from well dated stratigraphic contexts for Mesoamerica. Previously designated Lowe, these artifacts share multiple features with contemporary North and South American Paleoindian tool types. Once hafted, these bifaces appear to have served multiple functions for cutting, hooking, thrusting, or throwing. The tools were developed at a time of technological regionalization reflecting the diverse demands of a period of pronounced environmental change and population movement. Combined stratigraphic, technological, and population paleogenetic data suggests that there were strong ties between lowland neotropic regions at the onset of the Holocene.